Clinicopathological Study of Cystic Lesions of Pancreas at A Tertiary Care Center - Mundath, Vani; Kachappilly, Jeena Sam; Kizhakkethara, Geetha (Annals of Pathology and Laboratory Medicine, 2018)
Background: Cystic lesions of pancreas though uncommon are being increasingly identified as a result of developments in imaging techniques. Rapid advances in pancreatic surgeries associated with better patient outcome have led to a variety of pancreatic lesions being increasingly resected and pathologically diagnosed. Newer entities and classification systems have emerged. Methods: This was a hospital based study conducted in the Department of Pathology, Academy of Medical sciences, Pariyaram. In the 91pancreatic resections done over a period of 3 years from 2013-2016, there were 15 cases of cystic pancreatic lesions which formed the subject of the present study. Result: Cystic pancreatic lesions constituted 16.5% of cases (15 cases) of the 91 pancreatic resections done for various reasons. Of the 15 cases, there were 4 non-neoplastic cysts all of which were pancreatic pseudocysts with a M:F ratio of 3:1. There were 11 neoplastic cystic lesions with 4 serous cystadenomas, 3 solid papillary pseudotumors, 2 mucinous cystadenomas and 1 case each of invasive adenocarcinoma in Intraductal Papillary Mucinous Neoplasm (IPMN) and IPMN with low grade dysplasia Except for the one patient with invasive adenocarcinoma in IPMN all others with neoplastic lesions were females. Age of the patients ranged from 14-67 yrs. Conclusion: Cystic tumors of the pancreas are more common in females with the majority of the tumors being benign when compared to ductal adenocarcinomas which are aggressive tumors with higher incidence in males. The possibility of Solid papillary pseudotumor should always be considered in young females presenting with an encapsulated pancreatic mass especially in the tail of pancreas.